2022
DOI: 10.1063/5.0089099
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature electrical conductivity in piezoelectric lithium niobate

Abstract: Lithium niobate is a promising candidate for use in high-temperature piezoelectric devices due to its high Curie temperature ([Formula: see text]1483 K) and strong piezoelectric properties. However, the piezoelectric behavior has, in practice, been found to degrade at various temperatures as low as 573 K, with no satisfactory explanation available in the literature. We, therefore, studied the electrical conductivity of congruent lithium niobate single crystals in the temperature range of 293–1273 K with an 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Using the data from the Y-cut and Z-cut samples with the analytical model gives the complete set of elastic, piezoelectric, and dielectric coefficients in Table 3. The gradual increase of electrical conductivity at higher temperatures, particularly above about 500 °C, is consistent with the previously reported observations confirming the gradual appearance of ionic conduction caused by Li+ ion motion [14]. As is expected for any real material in the absence of a phase transformation or chemical reaction, the elastic stiffness coefficients are found to decrease with temperature.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Using the data from the Y-cut and Z-cut samples with the analytical model gives the complete set of elastic, piezoelectric, and dielectric coefficients in Table 3. The gradual increase of electrical conductivity at higher temperatures, particularly above about 500 °C, is consistent with the previously reported observations confirming the gradual appearance of ionic conduction caused by Li+ ion motion [14]. As is expected for any real material in the absence of a phase transformation or chemical reaction, the elastic stiffness coefficients are found to decrease with temperature.…”
Section: Resultssupporting
confidence: 91%
“…Of these candidates, lithium niobate is one of the most promising, because it combines a high Curie temperature of about 1210 °C with large piezoelectric coefficients [5][6][7] and is compatible with existing ultrasound technology [8,9]. Nonetheless, the experimental observation of piezoelectricity in LiNbO 3 has been found to often degrade well below the Curie temperature [10][11][12][13]; this has recently been confirmed to be caused by internal shorting of the crystal from the apparition of electrical conductivity at elevated temperatures dominated by Li+ ion motion [14]. Although this phenomenon can be mitigated through the implementation of appropriate design strategies, practical application of LiNbO 3 remains complicated by the poorly characterized material properties at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…These observations were recently confirmed to be caused by internal shorting of the crystal due to electrical conductivity at elevated temperatures dominated by Li+ ion motion and the composition of the LiNbO element. However, it was shown that it may be overcome by operating at a high frequency (>MHz) and choosing a monocrystal or a stoichiometric element [ 16 ]. The complete set of elastic, piezoelectric and dielectric coefficients has been evaluated from room temperature to 900 C [ 17 , 18 ].…”
Section: Transducer Designmentioning
confidence: 99%